Menjadikan PAI Menyenangkan Melalui Model MPA dengan Media Migami di SMAN 1 Peukan Bada - Yani, Muhammad; Rahmi, Siti (Jurnal Nispatti, 2024)
This study aims to improve student activity and learning achievement in Islamic Religious Education (PAI) through the application of the Market Place Activity (MPA) learning model combined with Migami (Miniature Origami) media. The background of this study is the low interest and involvement of students in PAI learning which is often considered monotonous and uninteresting. Classroom action research (CAR) was conducted in two cycles with the stages of planning, implementation, observation, and reflection. The subjects of the study were grade X students of SMAN 1 Peukan Bada. The instruments used included activity observation sheets, field notes, documentation, and learning outcome tests. The results showed a significant increase in student activity and involvement. In cycle II, students were more active in moving, discussing, exchanging information, and showing courage in explaining the material to peers. Migami media has been proven to help students understand concepts visually and concretely, so that the learning process becomes more interesting and meaningful. The increase in learning achievement is also seen from the increase in the final test scores of the cycle compared to the pre-cycle and cycle I. These findings confirm that the application of the MPA model with Migami media is effective in creating active, creative, and enjoyable PAI learning. This method is recommended for use in other Islamic Education materials and subjects that require collaborative and experience-based learning.